Amplification of minute amounts of oral bacterial DNA for real-time quantitative PCR Analysis - Wolff, Diana; Staehle, Hans Jörg; Wolff, Björn (Caries research, 2010)
Background: High-throughput technologies for typing caries or health-associated bacterial populations including PCR, DNA microarrays and next-generation sequencing techniques require significant amounts of bacterial DNA. In clinical settings, the amount of sampled DNA is often limited and amplification is therefore essential. Protocols should be able to reproducibly amplify sequences in order to maintain initial sequence ratios and should not bias the representation of particular DNA sequence types. Methods: A linear amplification protocol using DNA polymerase I was modified to permit the amplification and subsequent analysis of small amounts of bacterial DNA. The protocol was tested on human oral bacterial biofilms from different sources, including carious dentine and plaque, and compared to amplification by degenerate PCR of 16S rDNA sequences. Real-time quantitative PCR of 24 bacterial species was used as a readout system to test amplified DNA against unamplified DNA. Results: The amplification protocol reliably yielded 5-10 µg DNA from as little as 12.5 ng of template DNA. Correlation coefficients between real-time quantitative PCR results from amplified and unamplified DNA were between 0.78 and 0.98. Conclusion: The optimized protocol consistently produced amplification products from minute amounts of bacterial DNA from caries and plaque; the amplification products are suitable for downstream genetic analyses.